Leishmaniose Visceral canina: Clonagem e expressão das proteínas Lc24 e Lc36 de L. chagasi com potencial aplicação no diagnóstico e desenvolvimento de vacina - Isabel, Thais Ferreira [UNESP] (2010)
Canine visceral leishmaniasis (CVL) is the most severe clinical form of the disease and can be fatal if untreated. A specific and accurate diagnosis is required for the identification of infected dogs to provide better epidemiological control and earlier treatment. The more accurate diagnosis test is important especially in Brazil where infected animals are euthanized. Discordance among investigators regarding the accuracy of the tests currently employed for this purpose. This works reports the isolation, expression and test of two specific genes of Leishmania infantun (syn = chagasi), as a potential epitope for the development of a new diagnosis method and vaccine. The partial sequence of the genes rLc 24 and rLc36 was amplified with specific primers, cloned, and expressed in E. coli. The rLc 24 and rLc36 recombinant proteins was purified by GST affinity chromatography. Different concentrations of proteins were tested by Dot blot using a serum pool from infected dogs with leishmaniasis and a serum pool from dogs not infected. The protein concentrations of 0,1 and 0,01μg/mL were detected in the dot blot tests, showing that the protein rLc36 is immunoreaction and has potential to used in new diagnosis tests and development of vaccine.